2018
DOI: 10.1002/admi.201800249
|View full text |Cite
|
Sign up to set email alerts
|

Free‐Standing Bialkali Photocathodes Using Atomically Thin Substrates

Abstract: We report successful deposition of high quantum efficiency (QE) bialkali antimonide K2CsSb photocathodes on graphene films. The results pave a pathway towards an ultimate goal of encapsulating technologically-relevant photocathodes for accelerator technology with an atomically thin protecting layer to enhance lifetime while minimizing QE losses. A QE of 17 % at ~3.1 eV (405 nm) is the highest value reported so far on graphene substrates and is comparable to that obtained on stainless steel and nickel reference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 38 publications
2
20
0
Order By: Relevance
“…We previously demonstrated that K 2 CsSb photocathodes grown on graphene‐coated substrates exhibit X‐ray diffraction (XRD) and X‐ray fluorescence (XRF) spectra that are consistent with those obtained when using uncoated silicon substrates . These results indicate that both the crystal quality and elemental stoichiometry of K 2 CsSb photocathodes do not appreciably change due to graphene coating.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…We previously demonstrated that K 2 CsSb photocathodes grown on graphene‐coated substrates exhibit X‐ray diffraction (XRD) and X‐ray fluorescence (XRF) spectra that are consistent with those obtained when using uncoated silicon substrates . These results indicate that both the crystal quality and elemental stoichiometry of K 2 CsSb photocathodes do not appreciably change due to graphene coating.…”
Section: Resultssupporting
confidence: 68%
“…Optical profilometer measurements of the substrates indicated an average surface roughness of 230 nm, and grooves with an average maximum height of 1.4 μm and pitch of 15–50 μm. We previously demonstrated that free‐standing 2D crystals applied with these transfer techniques will naturally span large voids and still support K 2 CsSb photocathodes; thus, it is most probable that there are effective physical gaps between the photocathodes and the quite rough stainless steel substrates in this case as well.…”
Section: Resultsmentioning
confidence: 99%
“…The sample scatters light elastically, leading to nanometric features in the near field. This spatial light distribution is then converted, still in the near field, into a spatially varying electron flux via the photoelectric effect within a thin layer of low-workfunction photocathode (PC) material [27,28]. The emitted photoelectrons are then imaged using aberration-corrected low-energy electron optics [29,30].…”
Section: Conceptmentioning
confidence: 99%
“…The proposed technique would be intrinsically damage free. First, low-work-function photocathodes can be efficiently excited with green light [27] and thus at photon energies significantly below the absorption band of most proteins. The inset in Fig.…”
Section: Conceptmentioning
confidence: 99%
“…The first examples of successful integration of pristine few-layer graphene coatings with photoemission cathodes has occurred 110 in the form of atomically clean bulk copper (Gr : Cu) applied to graphene photocathodes 111 and the growth of high QE K 2 CsSb on suspended transparent graphene substrates 65,112 . In the copper study, the spectral response of the Gr : Cu system was measured as a function of the copper crystal face and thickness of graphene.…”
Section: Heterostructures In Cathode Materialsmentioning
confidence: 99%